2020
DOI: 10.1108/ijlma-06-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

Application of COSO framework in whistle-blowing activities of public higher-learning institutions

Abstract: Purpose The purpose of this study is to determine whether higher-learning institutions have sufficient internal controls to manage whistle-blowing or similar means when encountering repetitive complaints requiring similar corrective actions. This study attempts to classify complaints as per categories, criteria and components of the COSO framework using a checklist called self-assessment checklist of internal control kits so that complaint activities can be efficiently and effectively managed. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Those studies have been found in year 1998, 2003, 2012, 2015, 2017, 2018, 2019, 2020 and 2021 and the studies have been discovered through bibliometric search. Prevention and detection mechanisms such as internal control, data mining technology used to detect financial fraud and extensive knowledge and practice in Explain the Audit Procedure (EDP) as a part of fraud detection are all found to be the measures used to combat fraud (Abd Karim et al, 2018;Madi et al, 2021;Dangi et al, 2020;Zakaria et al, 2016;Azmi and Ismail, 2022;Alam et al, 2018;Muhamad and Gani, 2020;Ali et al, 2021;Musa et al, 2012;Aziz et al, 2021;Vanasco, 1998;Mwelu and Watundu, 2020;Quah, 2015;Alazzabi and Karage, 2020;Prenzler, 2019;Abramo and Brasil, 2003;Howell, 2017;Šnjegota, 2017;Iskandar, 2019;Al-Hashedi and Magalingam, 2021;Donning et al, 2019;Nawawi and Salin, 2018). Those researches were from the journal of financial crime, International Journal of Law and Management, Journal of Financial Reporting and Accounting, International Journal of Ethics and Systems, Journal of Finance and Risk Perspectives and Journal of Criminological Research, Policy and Practice.…”
Section: Fraud Prevention and Detection Mechanismsmentioning
confidence: 99%
“…Those studies have been found in year 1998, 2003, 2012, 2015, 2017, 2018, 2019, 2020 and 2021 and the studies have been discovered through bibliometric search. Prevention and detection mechanisms such as internal control, data mining technology used to detect financial fraud and extensive knowledge and practice in Explain the Audit Procedure (EDP) as a part of fraud detection are all found to be the measures used to combat fraud (Abd Karim et al, 2018;Madi et al, 2021;Dangi et al, 2020;Zakaria et al, 2016;Azmi and Ismail, 2022;Alam et al, 2018;Muhamad and Gani, 2020;Ali et al, 2021;Musa et al, 2012;Aziz et al, 2021;Vanasco, 1998;Mwelu and Watundu, 2020;Quah, 2015;Alazzabi and Karage, 2020;Prenzler, 2019;Abramo and Brasil, 2003;Howell, 2017;Šnjegota, 2017;Iskandar, 2019;Al-Hashedi and Magalingam, 2021;Donning et al, 2019;Nawawi and Salin, 2018). Those researches were from the journal of financial crime, International Journal of Law and Management, Journal of Financial Reporting and Accounting, International Journal of Ethics and Systems, Journal of Finance and Risk Perspectives and Journal of Criminological Research, Policy and Practice.…”
Section: Fraud Prevention and Detection Mechanismsmentioning
confidence: 99%
“…COSO's Concept of Internal Control was developed by collaborating with five private sector organizations to provide thought leadership for the framework and guidance for enterprise risk management, internal control and fraud and prevention. As this research provides suggestions and recommendations for internal control implementation of income-generating policies, the most appropriate is the internal control framework developed by COSO (Dangi et al. , 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Leadership quality can be a moderator of the ICS (Alam et al ., 2019; Dangi et al ., 2020) and FV (Imam and Reza, 2016; Miranda et al ., 2016). Previous research has found a relationship between ICSs and MIG (Adora, 2019; Towett et al.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accountability concepts play an important role and contribute significantly to the image and positive perceptions of government organizations and related workforce. In the private sector, accountability is important to ensure shareholder wealth and other stakeholder interests are properly safeguarded via ethical decision-making by top management (Alias et al, 2019;Salin & Ismail, 2015;Salin et al, 2020), transparent information disclosure (Jaafar et al, 2019;Salin et al, 2019), fraud prevention (Abidin et al, 2019), efficient corporate governance mechanisms (Nor et al, 2018;Shahar et al, 2020), and strong internal controls (Dangi et al, 2020;Karim et al, 2018).…”
Section: Public Sector Accountabilitymentioning
confidence: 99%